Beneficial effects of endoscopic screening on gastric cancer and optimal screening interval: a population-based study - Li, Wen-Qing; Qin, Xiang-Xiang; Li, Zhe-Xuan; Wang, Le-Hua; Liu, Zong-Chao; Fan, Xiao-Han; Zhang, Li-Hui; Li, Yi; Wu, Xiu-Zhen; Ma, Jun-Ling; Zhang, Yang; Zhang, Lan-Fu; Li, Ming; Zhou, Tong; Zhang, Jing-Ying; Wang, Jian-Xi; Liu, Wei-Dong; You, Wei-Cheng; Pan, Kai-Feng (Endoscopy, 2022)
Background The effectiveness of endoscopic screening on gastric cancer has not been widely investigated in China and the screening interval of repeated screening has not been determined.Methods In a population-based prospective study, we included 375,800 individuals, 14,670 of whom underwent endoscopic screening (2012–2018). We assessed the associations between endoscopic screening and risk of incident gastric cancer and gastric cancer-specific mortality, and examined changes in overall survival and disease-specific survival following screening. The optimal screening interval for repeated endoscopy for early detection of gastric cancer was explored.Results Ever receiving endoscopic screening significantly decreased the risk of invasive gastric cancer (age- and sex-adjusted relative risk [RR] 0.69, 95 % confidence interval [CI] 0.52–0.92) and gastric cancer-specific mortality (RR 0.33, 95 %CI 0.20–0.56), particularly for noncardia gastric cancer. Repeated screening strengthened the beneficial effect on invasive gastric cancer-specific mortality of one-time screening. Among invasive gastric cancers, screening-detected individuals had significantly better overall survival (RR 0.18, 95 %CI 0.13–0.25) and disease-specific survival (RR 0.18, 95 %CI 0.13–0.25) than unscreened individuals, particularly for those receiving repeated endoscopy. For individuals with intestinal metaplasia or low grade intraepithelial neoplasia, repeated endoscopy at an interval of < 2 years, particularly within 1 year, significantly enhanced the detection of early gastric cancer, compared with repeated screening after 2 years (P-trend = 0.02).Conclusion Endoscopic screening prevented gastric cancer occurrence and death, and improved its prognosis in a population-based study. Repeated endoscopy enhanced the effectiveness. Screening interval should be based on gastric lesion severity.